Serum 25‐hydroxyvitamin D increases with NB‐UVB and UVA/UVB phototherapy in patients with psoriasis and atopic dermatitis in Western Australia. (27th April 2015) - Le, Patricia; Tu, Jenny; Gebauer, Kurt; Brown, Suzanne
Abstract: Background/Objective: The benefit of NB‐UVB phototherapy on serum 25‐hydroxyvitamin D [25(OH)D] levels in patients with inflammatory skin conditions has been reported in the northern hemisphere. Vitamin D status is known to differ between geographical latitudes. The objective of this study was to investigate the influence of NB‐UVB and UVA/UVB phototherapy on the 25(OH)D serum levels in patients with psoriasis and atopic dermatitis in Western Australia. Methods: A total of 35 patients with psoriasis or atopic dermatitis requiring phototherapy thrice weekly for a minimum of 4 weeks were enrolled. Of these, 20 patients completed the study. Serum vitamin D levels were measured at baseline and at approximately 6 weeks into phototherapy. Data were adjusted for season, patients' age, sex, skin condition and Fitzpatrick skin phototype. Results: There was a statistically significant increase in serum 25(OH)D from pre‐ to post‐NB‐UVB and UVA/UVB phototherapy ( P < 0.0001), with a mean raw increase of 34.6 (25) nmol/L; or 45.1 (7.5) nmol/L when adjusted for covariates. This was also true for patients receiving NB‐UVB phototherapy with a baseline vitamin D of <80 nmol/L ( P < 0.05) and >80 nmol/L ( P < 0.004). Conclusions: NB‐UVB and UVA/UVB phototherapy significantly increased 25(OH)D serum level in patients with psoriasis and atopic dermatitis in Western Australia. Our study cohort had a higher baseline vitamin D level and a lower percentage increase of serum 25(OH)D post‐phototherapy than the increases reported in the literature from cohorts in the northern hemisphere.